Determinants of Mother Behavior in Disposing Household Garbage in Ternate City - Buamona, Sri Ayu; Handayani, Oktia Woro Kasmini; Laksono, Budi (Public Health Perspective Journal, 2021)
The garbage problem is increasing in line with the increase in population, especially in urban areas. Lifestyle and development impacts exacerbate the garbage problem. Poor management can have an impact on the health of residents, either due to pollution or flooding. The role of housewives in managing sampak at the family level is very important. The purpose of this study was to analyze the determinants of mother behavior in disposing of household garbage in Ternate City, North Maluku Province. This type of research is a quantitative study, using a correlation analytic research design and a cross sectional study design approach. The sample in this study amounted to 100 housewives. The instruments used were questionnaires, observation and checklist sheets. Data analysis This study uses path analysis techniques. The results showed that there was an effect of education on the behavior of mothers in disposing of household garbage in Ternate City, North Maluku Province, p-value of 0.000 <Î± (0.05). There is no influence of income p-value of 0.255> Î± (0.05). Cultural p-value is 0.749> Î± (0.05). And there is a perception effect of p-value of 0.042 <Î± (0.05). Education through perception is 35.2%, the rest is from other factors. Income through perception is 11.8%. Culture through perception of 31%. The conclusion from the study shows that the education and perception factors are more dominant and directly influence the behavior of mothers in disposing of garbage.